The Perception on the Importance and Practice of Top Management Commitment and Leadership in Palm Oil Industry Benchmarking Implementation - Fatimah, Mahmud; Baba, Md Deros; Dzuraidah, Abdul Wahab; Norazidah, Shamsudin (Advances in Global Business Research, 2015)
The palm oil industry is the backbone of Malaysian commodities market that contributed to the nation economic stability. In order to sustain and stay competitive, this industry needs to continuously improve its productivity and process efficiency. Benchmarking techniques can be used to identify and investigate palm oil industry best practices adopted by palm oil planters and millers. Past studies showed that the success of benchmarking initiative is very much dependent on top management’s commitment and leadership. This paper aims to discuss managers’ perception on the importance and actual practice of eight attributes of top management’s commitment and leadership in palm oil industry benchmarking implementation. A survey questionnaire was sent 700 middle managers involved in oil palm plantation and palm oil mill in Malaysia. The survey response rate was 49%. Analysis of the survey results shows significant differences between respondents’ perception on the importance and actual practice of the eight attributes of top management’s commitment and leadership. In other words, they have high perception of importance for the eight attributes; however, in reality the practice of attributes are still low. In conclusion, to ensure benchmarking implementation success, top management need to practice these attributes systematically.